2005
DOI: 10.1136/bjo.2004.057687
|View full text |Cite
|
Sign up to set email alerts
|

Neural progenitor cells from postmortem adult human retina

Abstract: Background: Given the presence of neural progenitor cells (NPC) in the retina of other species capable of differentiating into multiple neural components, the authors report the presence of NPC in the adult human retina. A resident population of NPC suggests that the retina may constitutively replace neurons, photoreceptors, and glia. Methods: Adult human postmortem retinal explants and cell suspensions were used to generate cells in tissue culture that display the features of NPC. The phenotype of cells and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 33 publications
4
60
0
2
Order By: Relevance
“…These data provided evidence that non-heart-beating donors could be a suitable source of hepatocytes for much longer time periods than previously thought possible [36]. It has also been shown previously that split-thickness skin grafts could be allografted up to 3 weeks after death if stored at 4°C [37], a fact that supports the idea that not only adult differentiated cells survive in the inner mileu of these organs and tissues but also probably stem cells [16]. Human induced pluripotent stem cells (iPSCs) have become also an intriguing approach for neurological disease modeling, because neural lineage-specific cell types that retain the donors' complex genetics can be established in vitro.…”
Section: Bone Marrow and Other Cadaver Sites For The Obtention Of Viasupporting
confidence: 77%
See 1 more Smart Citation
“…These data provided evidence that non-heart-beating donors could be a suitable source of hepatocytes for much longer time periods than previously thought possible [36]. It has also been shown previously that split-thickness skin grafts could be allografted up to 3 weeks after death if stored at 4°C [37], a fact that supports the idea that not only adult differentiated cells survive in the inner mileu of these organs and tissues but also probably stem cells [16]. Human induced pluripotent stem cells (iPSCs) have become also an intriguing approach for neurological disease modeling, because neural lineage-specific cell types that retain the donors' complex genetics can be established in vitro.…”
Section: Bone Marrow and Other Cadaver Sites For The Obtention Of Viasupporting
confidence: 77%
“…In this way, it is reasonable to expect that very soon, there will be studies to improve on the isolation procedures of different types of cadaver stem cells [10]. Therefore, it seems that it will be possible to routinely obtain stem cells of this kind from almost any human organ or tissue as desired [3,[16][17][18][19][20][21][22]. The procurement of different stem cell types from other sources beside living donors is a true possibility that needs to be explored [23].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are evidences that retina also contains precursor cells, detected by nestin staining, that continue to produce new neurons during post-natal development and adulthood (Johns 1977;Turner and Cepko 1987;Perron and Harris 2000;Mayer et al 2005) the role of NPY on retinal precursor cells proliferation is unknown.…”
mentioning
confidence: 99%
“…The observation of nestin-positive cells in CMZ as well as in radial cells within the retina infers the presence of progenitor cell populations within the retina as well as that of cells capable of directing migration of cells within the tissue towards cell renewal. 44,45 Others have also described from an immortalised Muller glia cell line the potential of cell depots with progenitor cell potential. 46,47 Further, our initial observations demonstrated that cells from epiretinal membranes of surgical specimens expressed nestin.…”
Section: Retinal Progenitor Cellsmentioning
confidence: 99%